Iron fortification of alugbati (Basella rubra L.) leaves using coconut milk protein-based emulsion. - Si, Kenneth Wilson A.
Effectiveness of Coconut Milk Protein-Based Emulsion in increasing the total iron concentration of alugbati (Basella rubra L.) leaves was tested in the experiment. Using an Atomic Absorption Spectrophotometry (AAS), total iron concentrations of oven-dried, digested alugbati samples were calculated after application of prepared foliar iron solution (treatment 1) and iron emulsion (treatment 2) sprays. From the results, it was revealed that the emulsion with 15% coconut milk protein forms smaller droplets and must be used to create the best emulsion to be used for the fortification process. Likewise, results showed that there was a significant increase in iron concentration on plants treated with the iron foliar sprays. Furthermore, Two-way ANOVA with Waller-Duncan Post Hoc statistical analysis revealed that the iron concentration of the control treatment was significantly different from the iron concentrations of treatment 1 and 2. Also, the plant treated with the emulsion-based spray for 1 day exhibited the best result. Generally, the emulsion-based folia spray is effective in raising the iron concentration of alugbati and can be used generally to fortify iron to other plants to support iron dietary needs.